ACTR-40. PHASE 2 SAFETY AND EFFICACY OF AR-67 (7-T-BUTYLDIMETHYLSILTYL-10-HYDROXYCAMPTOTHECIN) IN PATIENTS WITH RECURRENT GLIOBLASTOMA MULTIFORME (GBM) OR GLIOSARCOMA. (11th November 2019) - Kumthekar, Priya; Raizer, Jeffrey; Cavaliere, Robert; Devoe, Craig; Jensen, Randy; Stieber, Volker; Runk, Tina; Grewal, Jai; Brownell, Elise; Zukiwski, Alex; Proniuk, Stefan; Arnold, Susanne; et al.
Abstract: BACKGROUND: AR-67 (formerly DB-67) is a novel 3 rd generation camptothecin with improved safety and lipophilicity than current drugs in this class. Safety and efficacy of AR-67 were evaluated in a Phase 2 study in recurrent GBM/gliosarcoma in adult patients. METHODS: AR-67 (7.5 mg/m2) was administered once daily by IV infusion for 5 consecutive days on a 21-day cycle. Cohort 1 patients (N=31/46 enrolled) had not received (or had not recently failed) bevacizumab. Cohort 2 patients (N=13/46 enrolled) had failed bevacizumab within 90 days before screening. Cohort assignments for 2/46 patients were undetermined. Tumor response was assessed ≥14d after every second cycle and before every third cycle using MRI. Primary endpoints were 6-month PFS (Cohort 1), and 2-month PFS (Cohort 2). RESULTS: 45/46 patients received ≥ one dose of AR-67; one patient (Cohort 1) died prior to dosing. Efficacy: 6/30 (Cohort 1) and 2/13 (Cohort 2) treated patients achieved the primary endpoints of 6- and 2-month PFS, respectively. Across the study, PR was the best overall response in 3/45 treated patients, all in Cohort 1. SD was the best overall disease response in 7/45 treated patients (5 in Cohort 1 and 2 in Cohort2). Safety: AR-67 was well tolerated; 17 patients (38%) exhibited serious adverse events (SAEs) including headache and Grade 4/5 muscular weakness (2.2%). Most TEAEs were mild/moderate in intensity and Grade 1–3 intoxicity. Notably absent was Grade 4 diarrhea, a hallmark of other approved camptothecin chemotherapies. CONCLUSIONS: AR-67 was well tolerated and exhibited a safety profile consistent with or better than currently approved camptothecins. 6/30 treated patients in Cohort 1 and 2/13 patients in Cohort 2 achieved the primary endpoints of 6- and 2-month PFS, respectively. PR was the best overall response in 3/45 treated patients and SD was the best overall response in 7/45 patients.